Encyclopedia of survey research methods - Lavrakas, Paul J. (Los Angeles, California London SAGE, 2008)
Covers all major facets of survey research methodology, from selecting the sample design and the sampling frame, designing and pretesting the questionnaire, data collection, and data coding, to the issues surrounding diminishing response rates, confidentiality, privacy, informed consent and other ethical issues, data weighting, and data analyses--Publisher's website.
"A SAGE reference publication".
Keywords: Social surveys -- Research; Social surveys -- Methodology